PLACEMENT OF Syzygium boerlagei (Merr.) Govaerts (MYRTACEAE) CONFIRMED WITH atpB–rbcL INTERGENIC SPACER - Pudji Widodo; Tatik Chikmawati; Yayan Wahyu Candra Kusuma (BIOTROPIA, 2019)
A molecular analysis was conducted to determine whether Eugenia boerlagei Merr. (Myrtaceae) belongs to genus Eugenia or Syzygium based on sequences of cpDNA fragments namely atpB-rbcL intergenic spacer. The study used seven specimens of Syzygium sect. Jambosa, three of Syzygium sect. Syzygium, two of Eugenia s.s. and one of Eugenia boerlagei Merr. with Baeckea ovalifolia and B. tuberculata as the outgroup. The results show that Eugenia boerlagei is appropriately placed under the genus Syzygium.